AN ANALYSIS OF EFL STUDENTS’ WILLINGNESS TO COMMUNICATE (WTC) IN CLASSROOM AT A PUBLIC UNIVERSITY IN RIAU - Amelia, Riza (State Islamic University of Sultan Syarif Kasim Riau, 2025)
This study examines third-semester EFL students’ willingness to communicate (WTC) in the classroom using MacIntyre et al.’s (1998) WTC Pyramid model as the main framework. A descriptive research design was employed by administering a questionnaire consisting of close-ended items (5-point scale) and open-ended questions to 68 students in an English Education program at a public university in Riau Province, Indonesia. Quantitative data were analyzed descriptively to identify general tendencies across the WTC layers, while qualitative data were analyzed thematically to enrich and explain the quantitative patterns. The findings indicate that students reported moderate to high willingness to communicate; however, their actual classroom participation was often constrained by psychological barriers (e.g., nervousness, fear of making mistakes, and fear of negative evaluation), linguistic unpreparedness, and unsupportive peer responses. Students’ readiness and state self-confidence were higher when interacting with familiar classmates and topics but declined in less familiar contexts. Although students demonstrated strong motivational goals related to fluency development and future opportunities, these motivations did not consistently translate into speaking behavior when situational barriers were dominant. Overall, the results support the WTC Pyramid model by showing that classroom communication is shaped by interactions among multiple layers. Pedagogical implications highlight the importance of fostering psychologically safe classroom environments and strengthening students’ communicative confidence to enhance WTC.